THE PRESENT STATUS AND INTENSITY OF ECHINOCOCCUS GRANULOSUS INFECTION IN 391 STRAY DOGS IN RURAL AND URBAN AREAS OF THE CITY OF KERMAN, IRAN - I. Sharifi; N. Zia-Ali (Tehran University of Medical Sciences, 1996)
In the present study 6500 stray dogs were killed in 1993-4 to initiate a preliminary control program in rural and urban areas of the city of Kerman. 391 dogs including 169 (43.12%) females and 222 (56.8%) males were selected randomly, dissected and examined for Echinococcus granulosus and microscopically. The overall prevalence rate was 7.4%. The younger dogs were more susceptible to infection that the older ones. The prevalence of the worms was generally higher in female dogs than males. On the other hand, the mean number of worm recovery was 20 (light infection) in female dogs while it was 98 (moderate infection) in male dogs. Due to the hostile climatic and topographical conditions, echinococcosis was relatively low in this part of the country.